2019
DOI: 10.33225/jbse/19.18.117
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Mind Maps in Teaching Physics: Educational Efficiency and Students’ Involvement

Abstract: Primary school students generally lack motivation for learning physics, which they perceive as a difficult subject. In order to overcome this problem, it is necessary to apply appropriate teaching approach. The aim of this research was to assess the educational efficiency of mind maps in physics and students’ involvement when this approach is used. A pre-test – post-test control group design was used. The sample of this research consisted of 113 seventh-grade students divided into an experimental and a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
(36 reference statements)
1
9
0
1
Order By: Relevance
“…Previous research has revealed that students' success in physics subjects is lower than the biology and chemistry subjects (Bahar & Polat, 2007;Gagić et al, 2019). As the reasons for their difficulties in physics, students have stated that physics contains many abstract concepts, the concepts cannot be related to the daily life, and teachers mostly use direct instruction (Gagić et al, 2019). Therefore, students are often unmotivated to learn these concepts and they have difficulty in gaining meaningful learning.…”
Section: Research Problemmentioning
confidence: 99%
“…Previous research has revealed that students' success in physics subjects is lower than the biology and chemistry subjects (Bahar & Polat, 2007;Gagić et al, 2019). As the reasons for their difficulties in physics, students have stated that physics contains many abstract concepts, the concepts cannot be related to the daily life, and teachers mostly use direct instruction (Gagić et al, 2019). Therefore, students are often unmotivated to learn these concepts and they have difficulty in gaining meaningful learning.…”
Section: Research Problemmentioning
confidence: 99%
“…Penelitian oleh Marquez et al [19] menyebutkan bahwa sikap yang ditunjukkan oleh peserta didik selalu sangat positif, yang tercermin dalam hasil kuesioner kepuasan dengan sebagian besar peserta didik pada kelompok eksperimen merasa termotivasi oleh pengalaman selama proses pembelajaran. Implementasi mind map dapat meningkatkan motivasi belajar peserta didik [20].…”
Section: A) Efektivitas Berdasarkan Respon Mahasiswa Terhadap Penerapunclassified
“…During the seminars, we tested such interactive methods as analysis of specific situations, taskscases, group discussion, role-playing, brainstorming, games-dramatizations of real professional situations, quests, e-learning, mind-maps teaching, etc. (Gagic, 2019;Gianelli, 2018;Kicherova & Efimova, 2016).…”
Section: Resultsmentioning
confidence: 99%